Global burden and trends of chronic kidney disease due to type 2 diabetes mellitus caused by dietary risks: insights from the global burden of disease study 2021 - Wang, Xiaoyue; Yu, Yunfeng; Hu, Gang; Yang, Xinyu; Yin, Yuman; Zou, Junju; Yu, Rong (Frontiers in Endocrinology, 2025)
ObjectiveThe burden of dietary risk-induced diseases, including chronic kidney disease due to type 2 diabetes mellitus caused by dietary risks (CKD-T2DM-DR), has been consistently underestimated. This study aims to investigate the burden of CKD-T2DM-DR from 1990 to 2021 globally and regionally.MethodsThe global burden of disease (GBD) database served as the data source for analyzing the mortality, agestandardized mortality rate (ASMR), disability-adjusted life years (DALYs), age standardized DALY rate (ASDR), and estimated annual percentage change (EAPC) of CKD-T2DM-DR worldwide from 1990 to 2021. Subsequently, the ASMR, ASDR, and EAPC were further evaluated in different regions, age, gender, and socio-demographic index (SDI) groups. Finally, the burden of CKD-T2DM-DR induced by different dietary risks was reported and compared.ResultsGlobally, the mortality, ASMR, DALYs, and ASDR of CKD-T2DM-DR were on the rise from 1990 to 2021. The global mortality of CKD-T2DM-DR in 2021 was 79,988 (95% uncertainty interval [UI] 32,734–128,884), ASMR was 0.96 (95% UI 0.4–1.54) per 100,000 population, DALYs were 1,999,209 (95% UI 856,194–3,167,215), and ASDR was 23.21 (95% UI 9.95–36.61) per 100,000 population. Regionally, low SDI regions exhibited the highest ASDR (27.41 [95% UI 11.32–46.78] per 100,000 population) and ASMR (1.16 [95% UI 0.44–2.02] per 100,000 population), whereas high-middle SDI regions recorded the lowest ASDR (14.7 [95% UI 5.96–23.77] per 100,000 population) and ASMR (0.59 [95% UI 0.24–0.97] per 100,000 population). High SDI regions presented a rapid increase in ASDR and ASMR, with EAPCs of 1.02 (95% CI 0.86–1.19) and 1.4 (95% CI 1.23–1.58), respectively. The correlation analysis supported that ASDR and ASMR were negatively associated with SDI. Additionally, the global burden of CKD-T2DM-DR increased with age and was higher in men than in women. Among the seven associated dietary risks, the DALY and death percents of CKD-T2DM caused by diet low in fruit were the highest, at 4.57% and 4.31%, respectively.ConclusionThe global burden of CKD-T2DM-DR has been steadily increasing with significant regional variability. Low SDI regions are most severely affected by this challenge, while high SDI regions are experiencing a rapid increase in the burden. The diet low in fruit was identified as the primary dietary risk for CKD-T2DM. This highlights the urgent need for rapid growth in the targeted prevention and health care strategies to alleviate the global burden of CKD-T2DM-DR.